IMPLEMENTASI SISTEM PAKAR DIAGNOSA PENYAKIT AYAM BERBASIS WEB MENGGUNAKAN METODE CERTAINTY FACTOR (Science and Technology (SciTech), 2023)
A business cannot be separated from risks, including chicken farming, chicken is a food commodity that is currently quite promising to be made into a business and the majority of Indonesian people can consume it. However, there is a risk that chicken breeders are always afraid of, namely chicken disease, due to its massive spread when one of the chickens is sick, therefore the chicken breeder will use the services of a chicken expert to help overcome the disease problem, and this This of course burdens production costs. Therefore an expert system was developed that can diagnose chicken diseases and provide a solution using the certainty factor method, which of course the chicken expert system adopts the expertise or knowledge possessed by an expert.